A numerical study of the solidification process of a retracting fluid filament - Pham, Binh D.; Vu, Truong V.; Nguyen, Lien V. T.; Nguyen, Cuong T.; Nguyen, Hoe D.; Nguyen, Vinh T.; Vu, Hung V. (Vietnam Journal of Mechanics, 2021)
In this study, the retraction and solidification of a fluid filament are studied by a front-tracking method/finite difference scheme. The interface between two phases is handled by connected points (Lagrangian grid), which move on a fixed grid domain (Eulerian grid). The Navier-Stokes and energy equations are solved to simulate the problem. Initially, the fluid filament has a shape as half of a cylindrical capsule contact with a cold flat surface. We consider the effect of the aspect ratio (Ar) on the solidification of the fluid filament. It is found that an increase in the aspect ratio (Ar) in the range of 2 – 14 causes the retraction length to increase. The rate of the solidification of a fluid filament decreases when the Ar ratio increases. The solidification time, the solidification height and the tip angle of the fluid filament under the influence of the aspect ratio are also considered. After complete solidification, a small protrusion on the top of the solidified fluid filament is found.